11 A review of the impact of cardiovascular magnetic resonance on the management of inpatients at a tertiary referral centre. (28th January 2023) - Hampal, Rumneek; Knott, Kristopher D; Plastiras, Aristides; Bunce, Nicholas H
Abstract : Introduction: Cardiovascular Magnetic Resonance (CMR) is a highly versatile imaging modality, indicated in the assessment of most common cardiac presentations and is the gold standard for the assessment of cardiac chamber volume, tissue characterisation and myocardial perfusion. In this single UK tertiary centre study, we evaluated inpatient CMR referrals to investigate the impact on patient management. Materials and Methods: Patients who had an inpatient CMR between June to December 2021 were identified. Data collected included patient demographics, indication for CMR, CMR findings and whether patient management changed following the result. Results: There were 169 patients included within the study period. 66% were male. The mean age was 57.1 years. Primary indications for CMR included assessment of cardiomyopathies (53% patients), myocardial viability (17%) and suspected coronary artery disease (12%). Inpatient CMR led to an additional or complete change in diagnosis in 29% patients. The commonest diagnosis post-CMR was ischaemic heart disease (infarction/ischaemic cardiomyopathy, 34%). Non-ischaemic LV dysfunction was found in 23% scans, cardiomyopathy (including HCM, infiltrative cardiomyopathies) was detected in 12% and myocarditis was diagnosed in 11%. Discussion: This is the first study evaluating the use of inpatient CMR in the acute setting and the consequent impact on management at a tertiary centre. CMR changed patient management in 77% cases. This included medication changes, prompting further inpatient diagnostic tests or procedures (e.g.CRT/ICD) or hospital discharge. Interestingly in 6 cases, invasive coronary angiography was not performed due to the CMR result. Image quality was diagnostic (good or adequate) in 93% cine scans and in 87% of scans with late gadolinium enhancement (LGE). Overall CMR was well tolerated in 98% patients; there was one case of contrast extravasation. Conclusion: In this single, UK tertiary centre study we found that CMR impacted upon clinical management 77% of the time. CMR has become a vital tool in the management of cardiology inpatients particularly in the assessment of ischaemic heart disease, heart failure, cardiomyopathy and myocarditis.